Development of Psychology Program to Enhance life Skills Based on the Sufficiency Economy Philosophy for lowers Secondary Students in Muang District, Nakhon sawan - Saiyakul​, Mongkol​ (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2023)
The purposes of this study were 1) to investigate problems and essential needs to enhance the life skills of the secondary students based on philosophy of sufficiency economy, 2) to develop the psychology program for the secondary students and 3) to examine the effectiveness of the psychology program for the secondary students.The participants were 40 students at 3th level of secondary grade, who studied in the first semester, academic year 2019, in Suankularb Wittayalai (Jiraprawat) Nakhon Sawan School with life skills scores lower than the 25th percentile and voluntarily participating in the psychological program of 40 people. The research instruments were a questionnaire used to evaluate the students’ life skills based on sufficiency economy philosophy with reliability 0.7136 and the psychology program lasts for 2 days. Data were analyzed using mean dependent t-test. Research results were found as follows; 1) Considering the principles of sufficiency economy, it was found that the students had the problem with reasonableness, self-immunity, knowledge, along with virtue. 2) The results of developing a psychological program consisted of three stages which were introduction, process and conclusion. 3) After program completion, it was found that the students’ life skills based on philosophy economic sufficiency were improved with a significance level of 0.05.